Study on stability of microbial β-glucanase - ZHANG Xiu-yan; HE Guo-qing (浙江大学学报. 农业与生命科学版)
In order to improve the β-glucanase stability, the effect of different substances on β-glucanase stability was studied through single factor experiments, and the orthogonal experiment was used to optimize the complex protective agents. Finally, stability of enzyme with or without complex protective agents was measured. Results indicate that the albumin, glutin and CaCl2·H2O can enhance the enzyme stability. There is a remarkable synergistic effect when the three protective agents are mixed to use. The complex protective agents consists of 0.8% albumin (W/V), 2% glutin (W/V) and 1 mmol·L-1 CaCl2·H2O．The t1/2 value of enzyme with protective agents is 4℃ higher than that of enzyme with no protective agent. The thermal degradation rate is -0.0398 for enzyme with protective agent and -0.084 for enzyme with no protective agent at 36.2℃. The results above suggest that the complex protective agents can effectively enhance the thermostability and storage stability of β-glucanase.